Work Ideologies of Juvenile Probation Officers: The Effects of Individual Characteristics (Journal of Applied Juvenile Justice Services, 2023)
Probation is the oldest and most widely used community-based corrections program. Research on probation primarily focuses on the experiences of justice-involved juveniles and the supervision of juveniles in the probation system. Much less is understood about the impact probation officers' perceptions have on job performance and what factors influence those perceptions. The current study aimed to examine the relationship between individual characteristics (e.g., age, gender, race, level of education, tenure, political party affiliation, and jurisdiction) and juvenile probation officers' perceptions about their work ideology. Data for the study came from a sample of juvenile probation officers in nine states. Participants were asked questions about sanctioning, disposition, and role orientation. The study's findings show that few individual characteristics are significantly associated with attitudes/perceptions about work ideology. Probation officers’ race was the only predictor significantly associated with several outcomes. Implications and future directions for research are discussed.